The Dinastic Coin in the Decline in the Byzantine Empire: Ducas-Angelo, Comnenos and Paleologues - de Francisco Olmos, José María (Eikón / Imago, 2012)
In this article we analyze the question of throne succession in the Byzantine Empire from the 11th to the 15thcentury, where the idea of dynastical succession advances to the detriment of the providential succession, although the latter is still quite strong, as can be seen in Michel VIII’s accession, who justified his enthronement appealing to it. It will be shown how in the 9th century associations are kept in the coins, and the emperors reach the throne through marriage and manage to keep the succession rights their his sons. The accession of a new dynasty is characterised by its relation to the divinity that grants its continuity, as happened with the Komnenoi and the Palaeologi. The latter managed to consolidate and resist any usurpation attempt from other pretenders to the throne, that always had to look for some ties to the throne to be accepted (for instance the Kantakouzenoi).